Report of Haemophilus Influenzae serotype a intracranial infections in older children - Varvara Probst; Fadi Shahoud; Aaron Fletcher Osborne; Ana Alvarez; Nizar Maraqa; Ayesha Mirza (Wiley, 2023)
ABSTRACT Introduction Haemophilus influenzae (Hi) is subdivided into typeable (a-f) and non‐typeable groups. Hi serotype b (Hib) has historically been one of the important pathogens responsible for invasive infection. However, after widespread Hib vaccination, the emergence of other Hi serotypes, specifically Hi serotype a (Hia), was noted during the last few decades, mostly in children younger than 5 years of age. Case presentation We present two cases of severe intracranial infections with detected Hia in patients > 5 years of age within a short time frame and within the same geographic area. Conclusion Epidemiological studies and surveillance on Hia‐related illnesses in all age groups worldwide are needed to better understand the clinical and epidemiological characteristics of Hia. This can establish a platform to develop a candidate vaccine against Hia that might protect children of all ages.